Tubuh, Identitas, dan Tekanan Sosial: Konstruksi Citra Tubuh Remaja pada Media Sosial di Samarinda - Muhammad Arfan Hardiansyah M; Ismi Arsilah Rahmawati; Alifa Nabila Afaf; Gusti Rimarsha Nur Hidayah (Indonesian Journal Publisher, 2026)
Abstrak: Social media has become a primary space for adolescents in shaping identity and expressing themselves, particularly regarding body representation. In Samarinda City, this phenomenon presents unique complexities due to the intersection between strong local culture and the currents of digital globalization. This study aims to analyze adolescent body image construction practices on social media, identify the influence of global and local values on perceptions of the ideal body, and understand the digital social pressures experienced by adolescents. The research employs a qualitative approach using digital ethnography and in-depth interviews. Data were collected through observation of social media content (Instagram and TikTok) and in-depth interviews. Data analysis was conducted thematically using an interpretive approach. The findings reveal that: (1) adolescent body image on social media is constructive and strategic through a conscious curation process; (2) there is a negotiation between global values (beauty standards) and local values (religious norms, family, modesty) in shaping perceptions of the ideal body; (3) digital social pressure has varying impacts on individuals depending on factors such as self-confidence, social support, and value systems; (4) adolescents possess agency in managing their digital identity through protective strategies such as using private accounts and limiting audiences. This study contributes to the development of the anthropology of the body in digital spaces and serves as a foundation for developing school-based media literacy programs in developing regions. Keywords: Body Image; Identity; Social Media; Social Pressure; Anthropology of the Body.